PERBANDINGAN EFEKTIVITAS DAYA HAMBAT INFUSUM DAUN SIRIH (PIPERBETIE L) DAN DAUN MENGKUDU (MORINDA CITROFILIA L) TERHADAP PERTUMBUHAN JAMUR CANDIDA ALBICANS - Shara Lutfiyona Ikhsan; Detty Iryani; Nelvi Yohana (Andalas Dental Journal, 2014)
Many people tend to consider using plants for medicine. Beatle’s leaves are contained of some active substance such as kavikol,kavibetol and eugenol while mengkudu’s leave have active substance such as Scalopoetin ,antrhakuinon and saponin that known as antifungi. One of fungi as the main agent of Candidiasis diseases in mouth is Candida albicans. The purpose of study is to compairing the difference inhibitions activity of infusion beatle’s Leaves (Piper beatle L) and infusion mengkudu’s leaves (Morinda citrofilia L) against Candida albicans growth. The Study use dilution method to determine of Minimun Inhibitory Concentration (MIC). This research using 32 sample of infusion beatle’s leaves and infusion mengkudu’s leaves and mixing with Candida albicans and then incubation with Sabouroud Dextrose Broth media. The result is concentration 80% of infusion beatle’s leaves had an inhibitions power against Candida albicans growth. Concentration 100% infusion mengkudu’s leaves had an inhibitions power against Candida albicans growth.The Conclusion of the study is concentration needed of infusion beatle’s leaves low than infusion mengkudu’s leaves for inhibition against Candida albicans growth.